Sex specific impact of perinatal bisphenol A (BPA) exposure over a range of orally administered doses on rat hypothalamic sexual differentiation - McCaffrey, Katherine A. (2013)
Bisphenol A (BPA) is a high volume production chemical used in polycarbonate plastics, epoxy resins, thermal paper receipts, and other household products. The neural effects of early life BPA exposure, particularly to low doses administered orally, remain unclear. Thus, to better characterize the dose range over which BPA alters sex specific neuroanatomy, we examined the impact of perinatal BPA exposure on two sexually dimorphic regions in the anterior hypothalamus, the sexually dimorphic nucleus of the preoptic area (SDN-POA) and the anterioventral periventricular (AVPV) nucleus. Both are sexually differentiated by estradiol and play a role in sex specific reproductive physiology and behavior. Long Evans rats were prenatally exposed to 10, 100, 1000, 10,000 mg/kg bw/day BPA through daily, noninvasive oral administration of dosed-cookies to the dams. Offspring were reared to adulthood. Their brains were collected and immunolabeled for tyrosine hydroxylase (TH) in the AVPV and calbindin (CALB) in the SDN-POA. We observed decreased TH-ir cell numbers in the female AVPV across all exposure groups, an effect indicative of masculinization. In males, AVPV TH-ir cell numbers were significantly reduced in only the BPA 10 and BPA 10,000 groups. SDN-POA endpoints were unaltered in females but in males SDN-POA volume was significantly lower in all BPA exposure groups. CALB-ir was significantly lower in all but the BPA 1000 group. These effects are consistent with demasculinization. Collectively these data demonstrate that early life oral exposure to BPA at levels well below the current No Observed Adverse Effect Level (NOAEL) of 50 mg/kg/day can alter sex specific hypothalamic morphology in the rat.